Successful treatment of Giant keloid on the right toes using trepanation combined with superficial radiotherapy (SRT-100): a case report with literature review - Song, Ying-hua; Zhu, Hui-min; Chen, Dan; Qu, Zi-lu; Zhang, Liang; Wei, Li (Frontiers in Medicine, 2024)
In dermatology, a keloidKeloid is one of the most common skin morphological abnormalities caused by excessive proliferation of fibroblasts. in dermatology. Keloids that are largelarger or occur near important joint sites often cause varying degrees of physiological dysfunction in patients, therefore requiring medical treatment. A boy with congenital syndactyly had developed huge keloids at the surgical site after undergoing surgical correction treatment. After treatment using trepanation combined with superficial radiotherapy (SRT-100) in our hospital, most of the boy's keloids shrank and flattened. The; the affected foot had basically returned to its normal appearance, and the boy could wear shoes normallyas normal. The boy did not complain of pain, numbness, orand any other distinctivespecial discomfort after completingfinishing the treatment. This suggested that the combination of trepanation and superficial radiotherapy maymight be one of the alternative options for treating hypertrophic keloids that cannot be treated by surgical excision.